2015
DOI: 10.1371/journal.pone.0122281
|View full text |Cite
|
Sign up to set email alerts
|

Plants Probiotics as a Tool to Produce Highly Functional Fruits: The Case of Phyllobacterium and Vitamin C in Strawberries

Abstract: The increasing interest in the preservation of the environment and the health of consumers is changing production methods and food consumption habits. Functional foods are increasingly demanded by consumers because they contain bioactive compounds involved in health protection. In this sense biofertilization using plant probiotics is a reliable alternative to the use of chemical fertilizers, but there are few studies about the effects of plant probiotics on the yield of functional fruits and, especially, on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 41 publications
3
67
0
3
Order By: Relevance
“…Flores‐Félix et al . () used the term ‘plant probiotic’ to describe a Phyllobacterium which, as a root colonizer, improves strawberry plant growth and increases vitamin C content in the fruits. Hu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Flores‐Félix et al . () used the term ‘plant probiotic’ to describe a Phyllobacterium which, as a root colonizer, improves strawberry plant growth and increases vitamin C content in the fruits. Hu et al .…”
Section: Introductionmentioning
confidence: 99%
“…In similar work, where rhizobacteria with known growth promotion activity ( Bacillus OSU‐142, Bacillus M‐3 and Pseudomonas BA‐8) were inoculated into strawberries, a significant reduction in vitamin C was reported when compared to C samples . Moreover, a strain of the genus Phyllobacterium endophyticum inoculated into strawberry roots was able to increase the yield and quality of strawberry plants, also showing a significant increment in vitamin C content . Fasciglione et al inoculated Azospirillum brasilense into lettuce plants and reported a significant increase in ascorbic acid content (17.8 and 28.7 mg kg −1 for control and inoculated, respectively).…”
Section: Resultsmentioning
confidence: 94%
“…Vitamin C (or ascorbic acid) plays an important role in many physiological processes that are closely related to enzymatic activity, gene expression, environmental signaling and transport system in plants . In addition, it is a compound with proven antioxidant activity that in bell pepper is often very abundant . Another very important factor to consider is that vitamin C cannot be synthesized by the human body and is acquired through the diet, so any increase that could be achieved by agricultural practices is beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…The non-enzymatic antioxidant system is composed of several low-molecular-weight antioxidant molecules, such as AsA, which can directly eliminate ROS and regenerate ROS detoxifying enzymatic cooperative systems (Karahalil et al, 2015). AsA is a water-soluble antioxidant vitamin and a ubiquitous nutrient in eukaryotes (Bozonet et al, 2015; Flores-Félix et al, 2015). Fruits and vegetables are the major sources of ascorbate (Cruz-Rus et al, 2011; Ren et al, 2013).…”
Section: Introductionmentioning
confidence: 99%